Perceived positive mental health and resilience of grade 6 students - Claris Ann Baul; Arcel Cabasaan; Jollie Myr Dalisay; Jovenil Bacatan (Indonesian Journal of Social Sciences, 2023)
Positive mental health plays a pivotal role in overall health and wellness. The study aimed to determine the relationship between perceived positive mental health and resilience of grade 6 students in Tagbitan-ag Elementary School and to identify the levels of positive mental health and resilience. The study utilized a non-experimental quantitative correlational research design. The data was collected using an adapted survey questionnaire and was conducted on the selected 80 grade 6 learners employing convenience sampling. The data was analyzed using the Mean and Pearson-Product Moment Correlation Coefficient. The study results showed that grade 6 students had a moderately high level of perceived positive mental health and resilience. It was also found that perceived mental health is associated with the students' resilience. That suggests that individuals with higher levels of positive mental health are also more likely to have higher levels of resilience or vice-versa.